Vitamin B12 content of twenty percent saturated ammonium sulphate fraction proteins of red beet juice - (:unkn) unknown (My University, 2000)
B12 vitamini (siyanokobalamin) mikroorganizmalar tarafından yapılan bir vitamin olmasına rağmen hayvan gübresi kullanıldığı zaman bazı bitkilerin de sentez yapabildiği öne sürülmektedir. Kırmızı pancarda nispeten fazla miktarda B12 vitamini bulunması, bu bitkide B12 vitamini taşıyıcı ve bağlayıcı proteinlerin varlığını akla getirmektedir. Kırmızı pancar suyunun % 20'lik amonyum sülfat doygunluğunda çöken proteinleri, diyalizlendi ve liyofilize edilerek "Protein Karışımı " adı verildi ve buzdolabında saklandı. Bu protein karışımı DEAE selluloz kromatografısi ile daha ileri bir saflaştırmadan geçirildi ve en yüksek protein içeren fraksiyon "Protein 1" olarak adlandırldı. "Protein Karışımı " ve "Protein 1" deki B12 vitamini miktarları Lactobacillus leichmannii (ATCC 7830) bakterisi kullanılarak mikrobiyolojik olarak tayin edildi. Vitamin B12 bağlayan "Protein I'"in tamamen kolondan alındığı görüldü.

Vitamin B12 (cyanocobalamin) is one of the vitamins synthesised exclusively by microorganisms, although some reports claim that plants synthesize detectable amounts of vitamin B12, provided that animal manure is used. The presence of vitamin B12 relatively in high concentrations in red beet implies the presence of proteins that can bind and transport this vitamin. The soluble proteins of red beet juice were precipitated by twenty percent ammonium sulphate saturation, dialysed and concentrated by freeze drying and labeled as "Protein Mixture". This protein mixture was further purified by DEAE cellulose chromatography, the fraction containing the highest protein content was labeled as "Protein I". The vitamin B12 content of "Protein Mixture" and "Protein I" were determined by microbiological assay using Lactobacillus leichmannii (ATCC 7830). It appears that almost the total protein bounded by vitamin B12 was recovered from DEAE cellulose column.
Kırmızı pancar suyunun yüzde yirmilik amonyum sülfat doygunluğunda çöken proteinlerinin vitamin B12 miktarı